Interactions among dosage-dependent trans-acting modifiers of gene expression and position-effect variegation in Drosophila. - Bhadra, U.; Bhadra, M.P.; Birchler, J.A. (Genetics, 1998)
We have investigated the effect of dosage-dependent trans-acting regulators of the white eye color gene in combinations to understand their interaction properties. The consequences of the interactions will aid in an understanding of aneuploid syndromes, position-effect variegation (PEV), quantitative traits, and dosage compensation, all of which are affected by dosage-dependent modifiers. Various combinations modulate two functionally related transcripts, white and scarlet, differently. The overall trend is that multiple modifiers are noncumulative or epistatic to each other. In some combinations, developmental transitions from larvae to pupae to adults act as a switch for whether the effect is positive or negative. With position-effect variegation, similar responses were found as with gene expression. The highly multigenic nature of dosage-sensitive modulation of both gene expression and PEV suggests that dosage effects can be progressively transduced through a series of steps in a hierarchical manner.